INVENTARISASI TUMBUHAN BAWAH BERKHASIAT OBAT DI TAMAN NASIONAL DANAU SENTARUM KABUPATEN KAPUAS HULU PROVINSI KALIMANTAN BARAT Inventory Underground Plant as Source of Medicinal Plants from Danau Sentarum National Park Kapuas Hulu Regency West Kalimantan - Yanieta Arbiastutie (Tengkawang : Jurnal Ilmu Kehutanan, 2013)
Diversity of biological resources in primary forest is not only limited to the woody plant species, but also covered by underground plant which has diverse species high diversity. This underground plant as one part of the forest ecosystem is a plant that has potential as a medicine. The study aims to conduct an inventory of underground plant species in Danau Sentarum National Park Kapuas Hulu Regency West Kalimantan Province. The method used a plot inventory with studied area of ​​6 hectares, and sampling intensity of 0.4% across the sample plots with an area of ​​4 m2. Each rectangular-shaped sample plots with a size of 2 m x 2 m, and total number of sample plots was 50 plots. The sample plots are arranged systematically with distance between sample plots in a baseline was 10 m, while the distance between the baselines was 100 m. A line was made perpendicular to the river. The results showed there are 60 species underground plant which 42 species was a medicinal plants, 15 species was a shrubs, 27 species of herbs, ferns totaled 7 species, fungi consists of 4 species, 16 species of grass and 18 species was other underground plant. The Riang Bejid plant (Medinilla crassifolia) has the highest density value, frequency, INP and Shannon diversity index than other underground plants. The INP of Riang Bejid was 20.625%. Based on the test of phytochemicals, underground plant has secondary metabolites which contained alkaloids, flavonoids, saponins and sterols. This underground plant has a potential as medicine and anti-cancer. Keywords: Danau Sentarum National Park, inventory, medicinal plant, underground plant